2004
DOI: 10.1046/j.1365-2923.2004.01787.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing student reflection in medical practice. The development of an observer-rated instrument: reliability, validity and initial experiences

Abstract: Reflection in medical practice can be measured using this semistructured questionnaire built on case vignettes. The mean score allows for the measurement of improvement by future educational efforts. The wide range of individual differences allows for comparisons between groups. The differences found between groups of students were as expected and support the validity of the instrument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 10 publications
4
86
0
6
Order By: Relevance
“…In addition, the durations of Sobral's and our studies were 3 years and 1 year, respectively. Consistent with our findings, Boenink et al (2004) has observed a trend towards a lesser reflective ability. However, students in this study were more proficient in reflecting on their learning methods at baseline.…”
Section: Reflective Abilitysupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the durations of Sobral's and our studies were 3 years and 1 year, respectively. Consistent with our findings, Boenink et al (2004) has observed a trend towards a lesser reflective ability. However, students in this study were more proficient in reflecting on their learning methods at baseline.…”
Section: Reflective Abilitysupporting
confidence: 92%
“…Case scenarios are commonly used to elicit reflective responses in terms of professional judgement, ethical values and presumed moral behaviour in conflictual clinical situations (Boenink et al 2004;Norcini 2004). In this study, the themes depicted were patient confidentiality, trust and record keeping (Case Scenario 1), inappropriate consultant behaviour (Case Scenario 2), response to an emergency (Case Scenario 3) and clinical mismanagement by a senior colleague (Case Scenario 4).…”
Section: Methodsmentioning
confidence: 99%
“…Findings of increased stress levels have motivated a variety of interventions designed to provide sensitivity training (Dashef et al 1974;Hilberman et al 1975), self-awareness (Cadden et al 1969), self-reflection (Killion & Todnem 1991;Maudsley & Fryer-Edwards 2003;Boenink et al 2004), sharing of feelings and well-being (Dashef et al 1974;Coombs & Virshup 1994) discussion of roles as a physician improvement in health habits (Ball & Bax, 2002) and emotional competence (Flowers 2005) as mechanisms for reducing stress and improving coping skills. Observed outcomes included greater awareness of emotional issues in students, improved faculty/ student communication (Cadden et al 1969), less personal isolation and more sensitivity in communication among classmates (Dashef et al 1974).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…While medical teaching on self-reflection and professionalism is more wide spread in the UK (Maudsley & Fryer-Edwards 2003), curricula focusing on MBS and the promotion of self-awareness and self-reflection is less well established in medical schools in the United States (Dannoff & Corbet 2005). The learning objectives of self-awareness and reflection are often challenging to integrate into a medical school curriculum and equally difficult to assess (Boenink et al 2004). There have been a variety of interventions employed to help students alleviate stress, promote well-being and self-reflection, this paper describes the results of an experiential intervention focusing on MBS techniques to achieve these outcomes.…”
mentioning
confidence: 99%
“…Los e-diarios han sido utilizados para fomentar la práctica reflexiva en numerosos campos de la educación superior como por ejemplo trabajo social (Rutter, 2006), medicina (Boenink, Oderwald, De Jonge, Van Tilburg y Smal, (2004)), psicología (Jucks, Schulte-Löbbert y Bromme, 2007) o magisterio (Otienoh, 2009;Moon 2006Moon , 2010. La mayoría de estudios que utilizan el diario reflexivo online, lo hacen con el objeto de desarrollar y promover la práctica reflexiva entre el estudiantado tal y como puede revisarse en King y Kitchener (1994), Ross (1990) El diario online puede llevarse a cabo de manera interactiva y dialógica o de manera autobiográfica (Keating, 1993).…”
Section: El Diario Reflexivo Onlineunclassified